2021
DOI: 10.9734/jpri/2021/v33i59a34280
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Studies of Thiazole Ring Bearing Chalcone Derivatives

Abstract: Oxidative stress is one of the common problems seen in a variety of diseases. Chalcones and in particular heteroaryl chalcones had reported with promising antioxidant activities. Hence, in the present work, we reported the antioxidant activity of twenty thiazole ring bearing chalcone derivatives (1-20). Among the tested compounds, compounds 17, 19 and 20 containing 2-pyridinyl, 3-pyridinyl and 2-thiazolyl scaffolds showed superior antioxidant activity than the standard with their IC50 values 4±1µg/mL, 3±1 µg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The World Health Organization (WHO) reported that about a third of the world’s population is infected with M. tuberculosis . Kasetti and co-workers reported bioactive compounds containing thiazole and chalcone pharmacophores . All synthesized compounds were evaluated for their antitubercular activities by MTT assays.…”
Section: Biological Activities Of Chalcones Bearing An N-heterocyclic...mentioning
confidence: 99%
See 4 more Smart Citations
“…The World Health Organization (WHO) reported that about a third of the world’s population is infected with M. tuberculosis . Kasetti and co-workers reported bioactive compounds containing thiazole and chalcone pharmacophores . All synthesized compounds were evaluated for their antitubercular activities by MTT assays.…”
Section: Biological Activities Of Chalcones Bearing An N-heterocyclic...mentioning
confidence: 99%
“…A series of anticancer active thiazole-based chalcone derivatives 43 were reported by Kasetti and co-workers . Here, thiazole-carbaldehyde 41 was synthesized in three steps.…”
Section: Synthesis Of Chalcone Bearing An N-heterocyclic Scaffoldmentioning
confidence: 99%
See 3 more Smart Citations